1993
DOI: 10.1128/iai.61.5.1799-1809.1993
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of a high-molecular-mass major antigen of Helicobacter pylori: evidence of linkage to cytotoxin production

Abstract: A high-molecular-mass (120to 128-kDa) Helicobacter pyloni antigen has been associated with peptic ulcer disease. We created a bank of 40,000 random chromosomal fragments of H. pyloni 84-183 by using AZapII. Screening of this bank in Escherichia coli XL1-Blue with absorbed serum from an H. pyloni-infected person permitted the isolation and purification of a clone with a 3.5-kb insert. Subcloning of this insert (pMC3) permitted the expression of a recombinant H. pyloni protein that had a mass of approximately 96… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
294
0
2

Year Published

1994
1994
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 607 publications
(302 citation statements)
references
References 41 publications
4
294
0
2
Order By: Relevance
“…More than 18 years ago, Cover and co-workers reported a strong association between serologic responses to CagA and peptic ulcer disease (Cover et al, 1990). Independent observations led to cloning of the cagA gene (Tummuru et al, 1993;Covacci et al, 1993) and identification of the role of adjacent cag PAI genes in inflammation (Tummuru et al, 1995). One of these genes, picB (cagE), was recognized to encode a homologue of a protein involved in toxin export of Bordetella, which suggested that the cag PAI of Hp might play a role in secretion of yet unidentified products (Tummuru et al, 1995).…”
Section: Structure and Assembly Of The Type IV Secretion System Encodmentioning
confidence: 99%
“…More than 18 years ago, Cover and co-workers reported a strong association between serologic responses to CagA and peptic ulcer disease (Cover et al, 1990). Independent observations led to cloning of the cagA gene (Tummuru et al, 1993;Covacci et al, 1993) and identification of the role of adjacent cag PAI genes in inflammation (Tummuru et al, 1995). One of these genes, picB (cagE), was recognized to encode a homologue of a protein involved in toxin export of Bordetella, which suggested that the cag PAI of Hp might play a role in secretion of yet unidentified products (Tummuru et al, 1995).…”
Section: Structure and Assembly Of The Type IV Secretion System Encodmentioning
confidence: 99%
“…cagA genotyping of isolates was performed by PCR as described previously (Jenks et al, 1998). The CagA phenotype of isolates was determined by Western blotting with a CagA-reactive hyperimmune human serum (kindly donated by Professor M. J. Blaser, New York University Medical Center, NY, USA) (Tummuru et al, 1993).…”
Section: Molecular Characterization Of Isolatesmentioning
confidence: 99%
“…Antibodies to vacuolating toxin were no more prevalent in infected patients with vs. without ulcers, but antibodies to a 120-128 kDa protein were present in 100% of ulcer patients compared with about 70% of infected controls [71]. This protein has been cloned and the gene called cagA [8]. Studies indicate that strains with cagA express this and vacA whereas strains lacking cagA express neither.…”
Section: Toxinsmentioning
confidence: 99%